Association of TLR4 Polymorphisms, Expression, and Vitamin D with Helicobacter pylori Infection - Assaad, Shafika (J Pers Med, 2019)
Helicobacter pylori (H. pylori) infection is the strongest recognized risk factor for gastric adenocarcinoma. Since previous observations have shown that polymorphisms in innate immune system genes, as well as vitamin D (VitD) levels, could modify the risk of infection with Helicobacter pylori (H. pylori), we analyzed the relation between single nucleotide polymorphisms (SNPs) in TLRs (TLR1, TLR2, TLR4) CD14, RUNX3 and VitD levels with H. pylori infection. A case-control study on four hundred sixty Lebanese individuals was conducted. Eleven SNPs in total were genotyped and gene expression analysis using real-time PCR was performed in white blood cells of a subsample of eight individuals. A total of 49% of the participants were affected. Although no direct association was found between the SNPs and H. pylori infection, rs4986790G>A and rs4986791T>C in TLR4 were negatively associated with VitD levels (β = −0.371, p = 5 × 10(−3) and β = −0.4, p = 2 × 10(−3), respectively), which was negatively associated with H. pylori infection (OR = 0.01, p < 1 × 10(−3)). TLR4 expression was 3× lower in individuals with H. pylori compared with non-infected (p = 0.01). TLR4 polymorphisms, expression, and VitD could be implicated in H. pylori infection and further development of gastric adenocarcinoma.